Edible coatings based on hydroxypropyl methyl cellulose and beeswax in pinecone - Brasil, Yasmin Lima; Formiga, Anderson dos Santos; Cruz, Renata Ranielly Pedroza; Silva, Marcio Santos da; Silva, Alvaro Gustavo Ferreira da; Mattiuz, Ben-Hur [UNESP]; Costa, Franciscleudo Bezerra da; Ribeiro, Wellington Souto (Univ Federal Rural Pernambuco, 2022)
The pinecone (Annona squamosa L.) is an Annonaceae that provides much appreciated fruit. However, these fruits have a limited shelf life due to their intense metabolic activity after harvest. The application of post-harvest conservation techniques, such as edible coatings, has been used to minimize the deleterious effects after the harvest of fruits, such as pinecone. The objective of this work was to evaluate the effects of coatings based on hydroxypropyl methyl cellulose (HPMC) and beeswax (BW) on the quality of pinecones stored at room temperature of 20 degrees C, from the local market in the city of Juazeiro, BA, Brazil. The fruits were selected for the absence of damage and sanitized by immersion in chlorinated water. The coatings were prepared by diluting the HPMC solution in deionized water at 90 degrees C under stirring, followed by cooling and addition of BW in different proportions, stearic acid, and glycerol. The coatings were applied to the surface of the fruits by immersion in the film-forming solution and dried at room temperature of 20 degrees C. The HPMC-based coatings associated with BW maintained the firmness and the whitening index of the pulp of the cones for a longer time, as well as led to lower activity of the enzymes polyphenoloxidase (PPO) and peroxidase (POD) during storage.
Keywords: browning; coating; storage